Bombs over Biscay, Barcelona and Dresden (1937-1945): From the Spanish Civil War to the Second World War (Publicacions Universitat Rovira i Virgili, 2019)
Sometimes tragedies that have little to distinguish them from a wide range of similar events and which can make no claim to record numbers of casualties or destructive impact go down in history as fundamental and emblematic. This is the case of two of the airstrikes discussed in this volume: Barcelona and Dresden. Other tragedies, however, are sometimes obscured by circumstances elsewhere. This is the case of the "other Guernicas": that is to say, the bombings of Otxandio, Durango and Elorrio in Biscay. They are good examples not only of the brutality inherent in all wars and of how methods of combat become increasingly barbaric as conflicts wear on but also of the way in which some circumstances push events to the forefront of history and make them emblematic.